Ecosistemi letterari Luoghi e paesaggi nella finzione novecentesca - Turi, Nicola (Moderna/Comparata, 2016)
What does the growing interest of literary criticism towards the representation of nature and its ethical implications tell us? In which folds of narrative, poetic or cinematographic discourse do the manifestations of a continuously renewed sensitivity for the contradictions of progress, for the precarious coexistence between human, animal and plant agents lie? And what kind of relationships can there be between the semantics of places and landscapes, expressed in a fictional world, and eco-criticism? Sixteen essays suspended between 'text' analysis and theory of criticism are solicited and collected by Nicola Turi, in an attempt to answer these and other questions affecting the function and orientations of contemporary criticism, its ability to give back the forms of artistic language, and at the same time its recurring temptation to confront, as Calvino's Bradamante would say, with the «life behind it that pushes and disarranges all the leaves of the book».